A infância e o direito à cidadania: o reconhecimento da criança como sujeito histórico pela legislação brasileira- ECA/1990 e LDB/1996 - Silva, Débora Teodoro da (2022)
The history of childhood headed this master’s degree dissertation theme, and the line of research is History and Historiography of Education. The study focused on valuing the child, and having as guiding question, if the rights acquired and guaranteed in the Federal Constitution of 1988 and the subsequent complementary laws, especially the Statute of the Child and the Adolescent, were in fact guaranteed, and are actually being implemented in practice. Therefore, the research had as main objective to verify how the family, the school and the society observe the current legislation, how the society sees the child in the Brazilian contemporaneity, and if it is seen as a being that needs to be valued, that needs to have full conditions to develop as a being of rights, with the recognition of the importance of this phase in the individual's development process. Thus, this study sought to analyze the historical course of childhood, emphasizing the moment of modernity in which the individualization of childhood occurred, which Ariès called the childhood feeling, focused on physical and moral care for the small child. In the literature review, the analysis of the influence of social, cultural and economic context in the construction of pedagogical concepts linked to childhood was prioritized, as well as the emergence of the childhood feeling, which succeeded a concept of a child seen as an adult in miniature. This stage of Western modernity culminated in the childhood schooling. In the methodology, bibliographic research and documental research were used, an analysis was established in the light of the theoretical framework constituted by works on social history and the history of education. By this analytical instrument, the main documents related to the dissertation theme were highlighted, namely, the Law of Directives and Bases of National Education of 1996 and the Statute of the Child and Adolescent of 1990. The research theme allowed us to assess the evolution appreciation of childhood and the recognition of children’s specificities and individualities. Another valuable instrument in the research was the consultation of official websites which, besides bringing updated legislation, also enabled the collection of information regarding public policies and programs for children, implemented by the three spheres of government. Here another sensible issue about the protection of children emerged: the eradication of the child labor exploitation, which was also a way led by the studies. The research result was the verification of considerable advances in the process of valuing childhood, such as the recognition of early childhood education as the first stage of basic education, brought by the LDB/1996. Regarding the ECA/1990, it was a hit as a legal and regulatory frame for the human rights of children and adolescents, but the legislation does not work effectively, such as the eradication of the exploitation of child labor, which has made progress, but has also recently had setbacks and still counts on with a big fight ahead. Therefore, it is recommended for future research to go deeper into the instances of formulation, deliberation and control of public policies for children and adolescents, which guide the inspection of compliance with constitutional precepts and regulations in the complementary laws analyzed here.